2019
DOI: 10.1017/s0950268819001122
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific differences in the risk of hospitalisation among patients infected with hepatitis E virus genotype 3 in Belgium, 2010–2018

Abstract: Some European countries recently reported an increase in hepatitis E virus genotype 3 (HEV-3) of the subtype 3c. No link between HEV-3 subtypes and severity is established to date. Here, we report that patients infected with HEV-3c were at lower risk of hospitalisation, compared to those infected with HEV-3f, the other main subtype circulating in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
(14 reference statements)
1
29
0
Order By: Relevance
“…A correlation between GT3 subtypes and pathogenicity of acute hepatitis E disease was not observed, perhaps a consequence of the limited datasets. Moreover, it was difficult to compare our findings with data reported in the literature from other European countries, since prior reports did not evaluate symptomatic and asymptomatic patients separately [ 39 ] or comorbidities were not taken into account [ 40 ]. Italian zoonotic strains have often been genotyped by sequencing non-overlapping regions with our sequence target; thus, a comparison between human and animal HEV sequences was limited and was considered to be preliminary in our study.…”
Section: Discussionmentioning
confidence: 87%
“…A correlation between GT3 subtypes and pathogenicity of acute hepatitis E disease was not observed, perhaps a consequence of the limited datasets. Moreover, it was difficult to compare our findings with data reported in the literature from other European countries, since prior reports did not evaluate symptomatic and asymptomatic patients separately [ 39 ] or comorbidities were not taken into account [ 40 ]. Italian zoonotic strains have often been genotyped by sequencing non-overlapping regions with our sequence target; thus, a comparison between human and animal HEV sequences was limited and was considered to be preliminary in our study.…”
Section: Discussionmentioning
confidence: 87%
“…So that autochthonous HEV infection was represented, we actively excluded patients with a recent travel history to Africa or Asia, which are areas endemic for HEV G1 and 2. At the time of writing, a more detailed study of Scottish HEV phylogeny is currently underway could be important as a study of G3 cases in Belgium showed that there was a significantly lower rate of hospital admissions from HEV 3c subtype infections when compared to subtype HEV 3f 32 …”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that asymptomatic blood donors and patients with symptomatic hepatitis E had similar subtype distributions but that the blood donors had lower virus loads . However, a recent report indicated that patients in Belgium infected with HEV‐3c are at lower risk of hospitalization than those infected with HEV‐3f . We therefore looked for differences in the severity of disease caused by subtype 3f and subtype 3c infections by analysing the clinical and biological parameters from French immunocompetent patients with an HEV infection.…”
Section: Introductionmentioning
confidence: 98%
“…hepatitis E virus, hospitalization, pathogenicity, subtype hospitalization than those infected with HEV-3f. 11 We therefore looked for differences in the severity of disease caused by subtype 3f and subtype 3c infections by analysing the clinical and biological parameters from French immunocompetent patients with an HEV infection.…”
Section: Introductionmentioning
confidence: 99%